EDUCATION 4.0 FRAMEWORK: ENRICHING ACTIVE LEARNING WITH VIRTUAL AND TECHNOLOGICAL TOOLS (Proceedings of the International Conference on Education, 2021)
Dataset does not exist anymore: Caratozzolo, P., & Alvarez-Delgado, A. (2021, October). Education 4.0 framework: Enriching active learning with virtual and technological tools. In Proceedings of the International Conference on Education (Vol. 7, No. 1, pp. 614-628).The dataset with the identifier http://doi.org/10.17501/24246700.2021.7160 was withdrawn
Keywords: Critical Thinking; Creativity; Higher Education; Educational Innovation